Comparison of non-directive counselling and cognitive behaviour therapy for patients presenting in general practice with an ICD-10 depressive episode: a randomized control trial. Issue 9 (July 2014) - King, M.; Marston, L.; Bower, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Most evidence in the UK on the effectiveness of brief therapy for depression concerns cognitive behaviour therapy (CBT). In a trial published in 2000, we showed that non-directive counselling and CBT were equally effective in general practice for patients with depression and mixed anxiety and depression. Our results were criticized for including patients not meeting diagnostic criteria for a depressive disorder. In this reanalysis we aimed to compare the effectiveness of the two therapies for patients with an ICD-10 depressive episode. Method Patients with an ICD-10 depressive episode or mixed anxiety and depression were randomized to counselling, CBT or usual general practitioner (GP) care. Counsellors provided nondirective, interpersonal counselling following a manual that we developed based on the work of Carl Rogers. Cognitive behaviour therapists provided CBT also guided by a manual. Modelling was carried out using generalized estimating equations with the multiply imputed datasets. Outcomes were mean scores on the Beck Depression Inventory, Brief Symptom Inventory, and Social Adjustment Scale at 4 and 12 months. Results A total of 134 participants were randomized to CBT, 126 to counselling and 67 to usual GP care. We undertook (1) an interaction analysis using all 316 patients who were assigned a diagnosis and (2) a head-to-head comparison using only those 130 (41%) participants who had an ICD-10 depressive episode at baseline. CBT and counselling were both superior to GP care at 4 months but not at 12 months. There was no difference in the effectiveness of the two psychological therapies. Conclusions We recommend that national clinical guidelines take our findings into consideration in recommending effective alternatives to CBT.